Uma defesa do contingente a priori - Gaboardi, Gregory (2017)
In this work we will consider whether rationalism is compatible with there being a priori knowledge of contingent truths and if in fact there can be such knowledge. In order to do so we will evaluate a series of arguments that composed the discussion of this subject in the last decades — such as the arguments from Kripke (2012), Hawthorne (2002) and Turri (2011). We will conclude that rationalism is compatible with the existence of a priori knowledge of contingent truths and that such knowledge can indeed exist.